Global capitalism crisis fueling coups and instability in Africa - Alhinho, Júlia (Frontiers in Political Science, 2023)
I will argue that the recent surge of coups in Africa, like past surges, are closely linked with the cyclic crisis of capitalism to which Africa is especially vulnerable. African economies are mostly extractive and are enormously dependent on imports for energy and food from the global north. Nearly 20 percent of African capital is owned by foreigners. (Picketty, 2017, p.87) This leads to extreme inequality and consequently political instability in countries where colonial borders are still under dispute and where political decolonization did not translate into economic decolonization. Furthermore, the premise that economic liberalization would bring democracy – pushed through structural adjustment programs – has been proven wrong. I will try to show that there is a pattern of coups matching capitalism crisis. I will look into the example of Guinea-Bissau to show this linkage between crisis and coups. The fact the military still lead these coups is due to paradoxical factors: the symbolic capital of the armed forces as “people’s revolutionary forces”; and the involvement of the military elite in a significant illicit economy which has become very important to the survival of global capitalism.